SENSITIFITAS KINERJA PASAR MODAL INDONESIA DAN NILAI TUKAR RUPIAH TERHADAP PENYEBARAN KRISIS ASIA - Setyastuti, Rini (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2007)
This paper tries to examine the impact of Asia crisis on Indonesian stock market and exchange rate. Despite Engle-Granger procedure and Johansen Criterion, error correction model (ECM) of the two variables are employed to simultaneously estimate the short run and the long run dynamics of the variables. Using monthly data covering the January 1995 to December 2006, empirical results showed that there is a cointegration between variables in the crises period but no cointegration before crises period. The result of ECM estimation proves there is a positive effect on the exchange rate when the Indonesian stock price increased and Thailand exchange rate appreciated. It is because the foreign investors enter the domestic stock market. In the crises period, we can prove that the depreciation of domestic currency and Thailand currency have a positive effect on the stock price in the long run. On the other hand, it is evident that there is a stable parameter of analysis.Keywords : Exchange Rate, Stock Price, Interest Rate, ErrorÂ Correction Model